Reclaiming Nyunyurâs Plantation by Sosoâs Village Society District Gandusari Blitar Regency 1964-2014 - Khasanah, Binti Itaul; Sasmita, Nurhadi (Publika Budaya, 2014)
Â Â ABSTRACT This article discusses the social movement of the Soso society in the land dispute between Nyunyur Plantation with PT. Kismo Handayani by employing collective behaviour theory of Neil J. Smelser the author used the shape and strategy of social movement observed in Soso society. About 25 years, they have tried to reclaim 100 hectares of land subject to land reform, which was controlled by PT Kismo Handayani. The land was obtained by Soso society by decree of the Minister of Agriculture and Agrarian Number: 49 / Ka. / 1964. They have done a variety of procedural actions such as demonstrations, mediation, hearing and etcetera they it did not work. Finally Soso society took reclaiming as the final strategy. Previously, the land has been given a replacement, but not too small. Negotiations with various parties were always deadlocked. The government never took the initiative to resolve the dispute through it. As a result, the people do reclaiming as a way to exploit the land. The reclaimed lands were used for farming and housing. During took the plantations occupy land occupation, they did not yet feel successful and safe but still haunted by the fear of getting evicted or repressive measures of the government, because according to the law the lands were not yet legally theirs and the dispute was not yet over. Keywords: Nyunyurs Plantation, reclaiming, Soso society